Poverty and turmoil are in the midst of poverty Huosheng's poems exulted - Najm, Suaad (Al-Adab Journal, 2023)
Poverty or destitution is a situation in which a person does not have enough material assets to meet his basic needs. Poverty is one of the stages of mystical behavior in ancient Persian literature, and the concept of poverty in contemporary Persian literature is one of the most important social problems. In this research, we will talk about one of the contemporary poets who addressed poverty as one of the social and economic problems of man. Among these poets, the poet Hoshang is Ebtihaj. Nicknamed "Shadow", he is one of the famous poets of the contemporary world of Iran, who has always shown sensitivity towards the situations and events of the society, which is a sign of a kind of commitment and idealism. Also, the poet complains about the economic and class situation and the unequal conditions of the poor class of the society, and the beautiful lover of each line ends with a strong song, the black image of the society fits these dry endings.